L-cysteine modified nano-silver electrocatalyst and application thereof
By developing L-cysteine modified nanosilver electrocatalysts in CO2 in situ electroconversion system, using amino functional groups and microwave heating processes, the shortcomings in product selectivity and utilization of existing catalysts are solved, and efficient CO2 conversion and green fuel preparation are achieved.
Patent Information
- Application Number
- CN202510372981.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-27
AI Technical Summary
The existing CO2 in situ electrocatalytic reduction catalysts have shortcomings in the target product selectivity and carbon-containing component utilization rate, and the lack of development of specific electrocatalysts leads to low product selectivity.
A L-cysteine modified nanosilver electrocatalyst was developed. By adding L-cysteine to the silver nitrate-ethylene glycol system, the adsorption capacity of active substances is improved by using amino functional groups, and nanosilver particles were prepared by microwave heating technology to improve the specific surface area and stability.
High selectivity and high stability of product CO in CO2 in situ electroconversion system are achieved, CO2 utilization rate is improved, and efficient green fuel is prepared.
Smart Images

Figure CN119870448A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon dioxide electrocatalytic reduction catalyst, in particular to an L-cysteine modified nano-silver electrocatalyst and application thereof, belonging to the technical field of carbon dioxide emission reduction resource utilization and electrocatalytic material synthesis. Background Art
[0002] The rapid development of modern industrial society and economic level has brought about a large consumption of fossil energy (coal, oil, natural gas, etc.). Every year, a large amount of carbon dioxide (CO2) is emitted into the atmosphere due to the combustion of fossil energy. In order to cope with the climate change caused by CO2 emissions, how to collect and utilize CO2 that has been emitted into the environment has also been a research focus in recent years. CCUS (CO2 capture, utilization and storage) technology is a complete set of technical systems for CO2 capture, utilization and storage processes. Combining electrochemical reduction with carbon capture technology and directly using carbon capture media as a carbon source for in-situ conversion of CO2 to produce green fuels can not only effectively avoid the low CO2 utilization rate caused by a large amount of unreacted CO2, but also skip the high energy density parts such as CO2 regeneration and purification and pressurization, reducing the total energy consumption of the process. It is the key to developing efficient and low energy consumption CO2 capture and value-added utilization technology.
[0003] Different from the traditional CO2 electrochemical reduction which uses direct input of CO2 as a reactant, CO3 2- / HCO3 - In the in-situ electroreduction process, the main reactant is CO2 generated in situ on the surface of the ion exchange membrane due to the transport of protons. For electrolyzers equipped with cation exchange membranes (CEM), protons are provided by the anode reaction, and for electrolyzers based on bipolar membranes (BPM), protons come from the water dissociation in the middle layer of the membrane. The CO2 generated in situ can be further converted into common CO2 electroreduction products such as CO, formic acid, methane and ethylene on the catalyst surface. However, the catalysts for the in-situ electrocatalytic reduction of CO2 currently mostly use commercial nanoparticles and porous metal electrodes, and there is a lack of research and development of specific catalysts. Summary of the invention
[0004] According to the prior art, the lack of development of specific electrocatalysts in the CO2 in-situ conversion system leads to low selectivity of the target product and low utilization of carbon-containing components. The purpose of the present invention is to develop an L-cysteine-modified nanosilver electrocatalyst with simple synthesis and controllable conditions, and to achieve high selectivity and high stability for the product CO in the CO2 in-situ conversion system by improving the adsorption capacity of the electrocatalyst for active substances.
[0005] The technical solution adopted by the present invention to solve the technical problem is: An L-cysteine-modified nano-silver electrocatalyst is prepared by the following method: S1. Dissolve silver nitrate in water to obtain a 0.05-100 mM silver nitrate solution, add it to ethylene glycol and stir evenly; the volume ratio of the silver nitrate solution to ethylene glycol is 1:(2-20); S2, adding L-cysteine to the mixed solution, stirring evenly and then heating with a microwave, washing the obtained solid with ethanol and ultrapure water by centrifugation at least three times, and drying in a vacuum drying oven to obtain nanosilver particles; The molar ratio of silver element to L-cysteine is 1:(0.01~10).
[0006] Preferably, the stirring in S1 is 700-1500 rpm, and the stirring is carried out at a temperature of 20-40° C. for 30-60 min; The microwave heating time in S2 is 30-60 minutes, the microwave power is 100-300W, and the heating temperature is 120-160°C; the drying in S2 is oven drying, the oven drying temperature is 80-100°C, and the time is 1-24 hours. It is further preferred that in S2, the microwave power is 150W, and the heating is performed at 120°C for 60 minutes.
[0007] Preferably, the molar ratio of silver element to L-cysteine in S2 is 1:(0.5~1).
[0008] Preferably, 10 mL of 0.1 M silver nitrate aqueous solution is added to 90 mL of ethylene glycol and stirred at 800 rpm for 30 min until uniformly mixed; 0.12 g of L-cysteine is added to the mixed solution.
[0009] A nano silver catalytic electrode is prepared by the following method: dispersing the L-cysteine modified nano silver electrocatalyst particles of the present invention in an appropriate amount of isopropanol, preparing catalyst ink with Nafion ionomer, wherein the amount of Nafion ionomer used is 10%±2% of the catalyst mass, ultrasonically dispersing the obtained catalyst ink, and spraying the catalyst ink on an electrode substrate until the catalyst loading reaches 0.5-4 mg / cm 2 , and obtain a nano silver catalytic electrode. The preferred catalyst loading is 1-2.5 mg / cm 2 .
[0010] Preferably, the electrode substrate is a carbon-containing electrode substrate such as carbon paper, carbon cloth, carbon felt, etc.
[0011] An application of the L-cysteine modified nano-silver electrocatalyst of the present invention in the in-situ electroconversion of CO2 to efficiently prepare CO, the application is: using the L-cysteine modified nano-silver electrocatalyst as a catalyst for the in-situ conversion of carbon dioxide to directly reduce carbonate or bicarbonate to carbon monoxide.
[0012] An application of the nano-silver catalytic electrode of the present invention in the in-situ electroconversion of CO2 to efficiently prepare CO, the application is: using the L-cysteine-modified nano-silver catalytic electrode as a working electrode, and applying it to a CO2 in-situ electroconversion system.
[0013] Preferably, the electrolyte used in the cathode chamber of the electrolyzer in the CO2 in-situ electroconversion system is a 0.5-3M potassium carbonate or potassium bicarbonate solution; the working electrode in the cathode chamber of the CO2 in-situ electroconversion system converts HCO3 in the cathode electrolyte under the action of the current. - and CO3 2- The carbon-containing components are directly converted into CO. During the reaction, no additional exogenous carbon-containing gas, such as CO2, CO, etc., is introduced into the cathode chamber. The current density of the CO2 in-situ electroconversion system is 10~1000mA / cm 2 .
[0014] Preferably, the electrolyzer device of the CO2 in-situ electroconversion system comprises an anode flow plate, an anode porous electrode, a diaphragm, a cathode porous electrode and a cathode flow plate which are tightly fitted in sequence, an annular sealing gasket is arranged between the anode flow plate and the cathode flow plate, and the anode flow plate and the cathode flow plate are connected by a double-headed threaded screw and a nut to form a sealed electrolysis chamber, the anode flow plate and the diaphragm are the anode chamber, and the cathode flow plate and the diaphragm are the cathode chamber; the anode flow plate is provided with an anode liquid inlet and an anode liquid outlet, the anode flow plate is provided with an anode liquid groove flow channel on one side close to the anode porous electrode, and the anode liquid groove The two ends of the flow channel are respectively connected with the anode liquid inlet and the anode liquid outlet; the cathode flow plate is provided with a cathode liquid inlet and a cathode liquid outlet, and a cathode liquid groove flow channel is provided on the side of the cathode flow plate close to the cathode porous electrode, and the two ends of the cathode liquid groove flow channel are respectively connected with the cathode liquid inlet and the cathode liquid outlet; the anode flow plate and the cathode flow plate are respectively provided with an anode pole ear and a cathode pole ear for connecting the two ends of direct current; the cathode working electrode is the L-cysteine modified nanosilver catalytic electrode described in the present invention, the substrate of the anode porous electrode is a porous nickel foam material, and the diaphragm is an ion exchange membrane.
[0015] The beneficial effects of the present invention are: The present invention uses L-cysteine added to the silver nitrate-ethylene glycol system to achieve local capture of active substances using amino functional groups, thereby improving the selectivity of the target product. In addition, the present invention uses a microwave heating process, and microwave energy directly acts on the internal molecules of the material, causing violent thermal motion inside the material, accelerating chemical reactions, and obtaining nano silver particles with high particle size uniformity to increase the specific surface area while avoiding agglomeration. In the CO2 in-situ electrical conversion system, the electrocatalyst provided by the present invention achieves high selectivity and high stability for the target product CO due to the advantages of uniform dispersion, large specific surface area, and multiple active sites. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 Surface morphology of the catalytic electrodes prepared in Comparative Example 1, Comparative Example 2 and Example 1; Figure 2 The PVP / conventional heating, L-cysteine / conventional heating and L-cysteine / microwave heating at 20 mA / cm2 in Example 1 were 2 Comparison of selectivity for CO at different current densities; Figure 3 The PVP / conventional heating, L-cysteine / conventional heating and L-cysteine / microwave heating at 20 mA / cm2 in Example 1 were 2 Comparison of CO2 utilization under different current densities Figure 4 The three electrodes in Example 2 with molar ratios of silver:L-cysteine = 2:1, 1:1, and 1:3 were tested at 120 mA / cm 2 Comparison of selectivity for CO at different current densities; Figure 5 The three electrodes with different microwave heating powers at 170 mA / cm in Example 3 2 Comparison of selectivity for CO at different current densities. DETAILED DESCRIPTION
[0017] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.
[0018] In the present invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0019] The reagents used in the following examples, unless otherwise specified, can be purchased from conventional biochemical reagent stores.
[0020] The CO2 in-situ electric conversion system described in the present invention has a specific structure, see the carbon pollution absorption liquid electric drive conversion unit P1 of CN 119075604 A patent name "A carbon pollution absorption liquid electrothermal catalytic green fuel preparation device and method", the electrolyzer device of the CO2 in-situ electric conversion system includes an anode flow plate, an anode porous electrode, a diaphragm, a cathode porous electrode and a cathode flow plate that are tightly fitted in sequence, an annular sealing gasket is arranged between the anode flow plate and the cathode flow plate, and the anode flow plate and the cathode flow plate are connected by a double-headed threaded screw and a nut to form a sealed electrolysis chamber, the anode flow plate and the diaphragm are between the anode chamber, and the cathode flow plate and the diaphragm are between the cathode chamber; the anode flow plate is provided with an anode liquid inlet and an anode liquid outlet, and the anode flow plate is close to the anode porous electrode. An anode liquid groove flow channel is provided on one side of the cathode, and the two ends of the anode liquid groove flow channel are respectively connected to the anode liquid inlet and the anode liquid outlet; a cathode liquid inlet and a cathode liquid outlet are provided on the cathode flow plate, and a cathode liquid groove flow channel is provided on the side of the cathode flow plate close to the cathode porous electrode, and the two ends of the cathode liquid groove flow channel are respectively connected to the cathode liquid inlet and the cathode liquid outlet; an anode electrode ear and a cathode electrode ear for connecting the two ends of direct current are respectively provided on the anode flow plate and the cathode flow plate; the cathode working electrode is the L-cysteine modified nanosilver catalytic electrode described in the present invention, the substrate of the anode porous electrode is a porous nickel foam material, and the diaphragm is an ion exchange membrane.
[0021] Carbon paper substrate, Freudenberg H23 carbon paper, commercially available.
[0022] Nafion ionomer, aqueous solution is Nafion TM The polymer dispersant is Nafion 117 solution (McLean N831951 Nafion 117 perfluorinated resin solution, ~5% in a mixture of lower aliphatic alcohols and water), Cas No.: 31175-20-9, commercially available.
[0023] Example: Preparation of L-cysteine modified nanosilver catalytic electrode and in-situ conversion of CO2 Example 1: Preparation of L-cysteine modified nanosilver catalytic electrode (L-cysteine / microwave heating): 10 mL of 0.1 M silver nitrate aqueous solution was added to 90 mL of ethylene glycol and stirred at 800 rpm for 30 min until uniformly mixed; 0.12 g of L-cysteine was added to the mixed solution and stirred until the L-cysteine was completely dissolved, the microwave power was set to 150 W, and the mixture was heated at 120° C. for 60 min. The obtained solid was centrifugally washed three times with anhydrous ethanol and ultrapure water, respectively, and dried in a vacuum drying oven at 100° C. for 12 h to obtain L-cysteine modified nanosilver particles; 105 mg of L-cysteine modified nanosilver particles were taken and dispersed in 20 mL of isopropanol, and catalyst ink was prepared with Nafion ionomer, the amount of Nafion ionomer used was 10% of the catalyst mass, and the obtained catalyst ink was ultrasonically dispersed for 60 min and then the catalyst ink was sprayed on a 2x0.5 cm 2 Carbon paper substrate, solid catalyst loading weight 1.0 mg / cm 2 , and obtain L-cysteine modified nanosilver catalytic electrode.
[0024] Comparative Example 1 Preparation of PVP-modified nanosilver catalytic electrode (PVP / ordinary heating): 10 mL of 0.1 M silver nitrate aqueous solution was added to 90 mL of ethylene glycol and stirred at 800 rpm for 30 min until uniformly mixed; 0.11 g of polyvinyl pyrrolidone (PVP) was added to the mixed solution, stirred until PVP was completely dissolved, placed in an oil bath, and heated at 120 ° C for 60 min. The obtained solid was centrifuged and washed three times with anhydrous ethanol and ultrapure water, respectively, and dried in a vacuum drying oven at 100 ° C for 12 h to obtain PVP-modified nanosilver particles. 105 mg of PVP-modified nanosilver particles were taken and dispersed in 20 mL of isopropanol. Catalyst ink was prepared with Nafion ionomer, and the amount of Nafion ionomer was 10% of the mass of the catalyst. The obtained catalyst ink was ultrasonically dispersed for 60 min and then the catalyst ink was sprayed on 2x0.5 cm 2 Carbon paper substrate, solid catalyst loading weight 1.0 mg / cm 2 , and obtain the PVP-modified nanosilver catalytic electrode.
[0025] Comparative Example 2: Preparation of L-cysteine modified nanosilver catalytic electrode (L-cysteine / ordinary heating): The specific method is the same as Example 1, except that the heating method is the same as that in Comparative Example 1, which is heating in an oil bath at 120° C. for 60 min.
[0026] The surface morphology of the catalytic electrodes prepared in Comparative Example 1, Comparative Example 2 and Example 1 is shown in FIG. Figure 1 , Figure 1 (a) is PVP / normal heating, Figure 1 (b) is L-cysteine / normal heating, Figure 1 (c) in the figure is L-cysteine / microwave heating. The average particle size of the nanosilver particles produced by PVP / conventional heating is 400nm, the average particle size of the nanosilver particles produced by L-cysteine / conventional heating is 50nm, but they are easily aggregated into nanoclusters with a particle size of 600-800nm, and the average particle size of the nanosilver particles produced by L-cysteine / microwave heating is 10nm, and they are evenly distributed without obvious cluster aggregation. Figure 1 It can be seen that the catalytic electrode prepared by microwave heating has the advantages of uniform dispersion and large specific surface area.
[0027] The L-cysteine modified nanosilver catalytic electrode was tested in a flow-type electrolytic cell: the catalytic electrodes prepared in Example 1, Comparative Example 1, and Comparative Example 2 were used as working electrodes, and Ni mesh was used as counter electrode. Electrochemical tests were performed in a flow-type electrolytic cell. The cathode electrolyte was 2M KHCO3, the anode electrolyte was 1M KOH, and the cathode chamber and the anode chamber were separated by a bipolar membrane. The flow rate was 20 mA / cm 2 The constant current test was carried out at a current density of 1.5 0.1 0.04 0.02 0.08 0.06 0.07 0.09 0.13 0.06 0.08 0.09 0.12 0.06 0.06 0.08 0.09 0.13 0.06 0.08 Figure 2 The CO Faraday efficiencies of the electrodes prepared by PVP / conventional heating, L-cysteine / conventional heating, and L-cysteine / microwave heating during the test were 29.0%, 41.0%, and 58.9%, respectively. The CO2 utilization rate can be calculated based on the CO and CO2 concentration ratios in the gas at the system outlet. The results are shown in Figure 3 The CO Faraday efficiencies of the electrodes prepared by PVP / conventional heating, L-cysteine / conventional heating, and L-cysteine / microwave heating during the test were 25.3%, 40.4%, and 55.0%, respectively.
[0028] Combination Figure 1 , Figure 2 The results show that compared with the L-cysteine-modified nanosilver catalytic electrode prepared by ordinary oil bath heating, microwave heating can achieve uniform heating of the entire material sample, rapid decomposition of the metal precursor, and obtain nanosilver particles with high particle size uniformity to increase the specific surface area while avoiding agglomeration. Compared with the test results of the catalytic electrode prepared by the silver nitrate-ethylene glycol system plus polyvinyl pyrrolidone (PVP) in the prior art, the selectivity for the product CO is higher. In addition, due to the local capture of active substances by the surface amino functional groups of the L-cysteine-modified nanosilver catalytic electrode, a higher CO2 utilization rate is achieved in the in-situ conversion of CO2.
[0029] Example 2: Preparation of Nanosilver Catalytic Electrodes Modified with Different L-Cysteine Ratios and In-Situ Conversion of CO2 1) Preparation of L-cysteine modified nanosilver catalytic electrode: 10 mL of 0.1 M silver nitrate aqueous solution was added to 90 mL of ethylene glycol and stirred at 800 rpm for 30 min until uniformly mixed; 0.06 g, 0.12 g, and 0.36 g of L-cysteine (the molar ratio of silver: L-cysteine was 2:1, 1:1, and 1:3, respectively) were added to the mixture, and stirred until L-cysteine was completely dissolved. The microwave power was set to 150 W and heated at 120 ° C for 60 min. The obtained solid was centrifugally washed three times with anhydrous ethanol and ultrapure water, respectively, and dried at 100 ° C in a vacuum drying oven for 12 h to obtain L-cysteine-modified nanosilver particles; 105 mg of L-cysteine-modified nanosilver particles were taken and dispersed in 20 mL of isopropanol, and catalyst ink was prepared with Nafion ionomer. The amount of Nafion ionomer was 10% of the catalyst mass. The obtained catalyst ink was ultrasonically dispersed for 60 min and then the catalyst ink was sprayed on a 2x2 cm 2 Carbon paper substrate, solid catalyst loading weight 1.0 mg / cm 2 , and obtain L-cysteine modified nanosilver catalytic electrode.
[0030] 2) Testing of L-cysteine-modified nanosilver catalytic electrode in CO2 in situ conversion system The three catalytic electrodes prepared in step 1) were used as working electrodes and IrO2 mesh as counter electrode. Electrochemical tests were carried out in a CO2 in-situ conversion system. The cathode electrolyte was 1.5M KHCO3, the anolyte was 0.01M H2SO4, and the cathode and anode chambers were separated by a Nafion proton exchange membrane. The current was 120 mA / cm 2 A constant current test was performed at a current density of 1.5 0.1 0.5 0.2 0.6 0.8 0.9 0.1 ...
[0031] Silver: L-cysteine = 2:1, 1:1, 1:3 molar ratio of three electrodes at 120mA / cm 2 The selectivity comparison results for CO at different current densities are shown in Figure 4 During the test, the CO Faraday efficiencies of the three electrodes with silver: L-cysteine = 2:1, 1:1, and 1:3 molar ratios were 66.5%, 75.6%, and 54.6%, respectively; Figure 4 The results show that the selectivity of the target product CO and the utilization rate of the carbon-containing components of the L-cysteine-modified nanosilver catalytic electrode first increase and then decrease with the change of the molar ratio of L-cysteine and silver source added during the reduction process, and the best performance is shown under the condition of a silver:L-cysteine molar ratio of 1:1.
[0032] Example 3: Preparation of L-cysteine-modified nanosilver catalytic electrodes prepared at different microwave heating powers and in-situ conversion of CO2 1) Preparation of L-cysteine modified nanosilver catalytic electrode: 10 mL of 0.1 M silver nitrate aqueous solution was added to 90 mL of ethylene glycol and stirred at 800 rpm for 30 min until uniformly mixed; 0.12 g of L-cysteine was added to the mixture, stirred until L-cysteine was completely dissolved, microwave powers were set to 100, 150, and 200 W, respectively, and heated at 120 ° C for 60 min. The obtained solid was centrifugally washed three times with anhydrous ethanol and ultrapure water, respectively, and dried at 100 ° C in a vacuum drying oven for 12 h to obtain L-cysteine-modified nanosilver particles; 105 mg of L-cysteine-modified nanosilver particles were taken and dispersed in 20 mL of isopropanol, and catalyst ink was prepared with Nafion ionomer, the amount of Nafion ionomer was 10% of the catalyst mass, and the obtained catalyst ink was ultrasonically dispersed for 60 min and then the obtained catalyst ink was sprayed on a 2x2 cm 2 Carbon paper substrate, solid catalyst loading weight 1.0 mg / cm 2 , and obtain L-cysteine modified nanosilver catalytic electrode.
[0033] 2) Testing of L-cysteine-modified nanosilver catalytic electrode in CO2 in situ conversion system The three catalytic electrodes prepared in step 1) were used as working electrodes and Ni mesh as counter electrode. Electrochemical tests were carried out in a CO2 in-situ conversion system. The cathode electrolyte was 1.5 M KHCO3, the anolyte was 1.5 M KOH, and the cathode chamber and the anode chamber were separated by a bipolar membrane. The current was 170 mA / cm 2 A constant current test was performed at a current density of 1.5 0.1 0.5 0.2 0.6 0.8 0.9 0.1 ...
[0034] Three electrodes with different microwave heating powers at 170 mA / cm 2 The selectivity comparison results for CO at different current densities are shown in Figure 5 During the test, the CO Faraday efficiencies of the three electrodes with microwave heating of 100W, 150W and 200W were 61.5%, 73.5% and 58.4% respectively. Figure 5 It can be seen that changes in microwave power during the reduction process will lead to changes in the performance of the catalytic electrode tested in the CO2 in-situ conversion system, among which a microwave power of 150W shows the best CO selectivity.
[0035] In summary, the present invention adds L-cysteine to the silver nitrate-ethylene glycol system and utilizes the modification of the amino functional group to achieve local capture of the active substance and improve the selectivity of the target product. By utilizing the microwave heating process, the microwave energy directly acts on the molecules inside the substance, causing violent thermal motion inside the material, accelerating the chemical reaction, and obtaining nanosilver particles with high particle size uniformity to increase the specific surface area while avoiding agglomeration. In the CO2 in-situ electroconversion system, due to the advantages of uniform dispersion, large specific surface area, and multiple active sites, the electrocatalyst provided by the present invention achieves high selectivity and high stability for the target product CO, and can directly electrolyze and convert carbonate or bicarbonate solutions into efficient synthesis of CO, realizing an efficient treatment process for short-process carbon reduction and emission reduction.
[0036] The L-cysteine modified nanosilver catalytic electrode prepared by microwave heating can improve the selectivity of the target product CO and enhance the utilization rate of carbon-containing components in the CO2 in-situ conversion system.
[0037] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0038] The above is a detailed introduction to a L-cysteine modified nano silver electrocatalyst and its application provided by the present invention. Specific examples are used herein to illustrate the principle and implementation of the present invention, and the description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for those of ordinary skill in the art, without departing from the principle of the present invention, the present invention can also be improved and modified in several ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. An L-cysteine modified nanosilver electrocatalyst, characterized in that The catalyst is prepared by the following method: S1. Dissolve silver nitrate in water to obtain a 0.05-100 mM silver nitrate solution, add it to ethylene glycol and stir evenly; the volume ratio of the silver nitrate solution to ethylene glycol is 1:(2-20); S2, adding L-cysteine to the mixed solution, stirring evenly and then heating with a microwave, washing the obtained solid with ethanol and ultrapure water by centrifugation at least three times, and drying in a vacuum drying oven to obtain nanosilver particles; The molar ratio of silver element to L-cysteine is 1:(0.01~10).
2. The L-cysteine modified nano-silver electrocatalyst according to claim 1, characterized in that: The stirring in S1 is 700-1500 rpm, and the stirring is carried out at a temperature of 20-40° C. for 30-60 min; The microwave heating time described in S2 is 30-60 min, the microwave power is 100-300 W, and the heating temperature is 120-160° C.; The drying described in S2 is oven drying, and the oven drying temperature is 80-100° C. and the time is 1-24 hours.
3. The L-cysteine modified nano-silver electrocatalyst according to claim 1, characterized in that: In S2, the microwave power was 150 W and the heating was performed at 120° C. for 60 min.
4. The L-cysteine modified nano-silver electrocatalyst according to claim 1, characterized in that: The molar ratio of silver element to L-cysteine in S2 is 1:(0.5~1).
5. The L-cysteine modified nano-silver electrocatalyst according to claim 1, characterized in that: 10 mL of 0.1 M silver nitrate aqueous solution was added to 90 mL of ethylene glycol and stirred at 800 rpm for 30 min until uniformly mixed; 0.12 g of L-cysteine was added to the mixture.
6. A nano silver catalytic electrode, characterized in that The nano silver catalytic electrode is prepared by the following method: The L-cysteine modified nanosilver electrocatalyst particles according to claim 1 are dispersed in an appropriate amount of isopropanol, and a catalyst ink is prepared with Nafion ionomer, wherein the amount of Nafion ionomer is 10%±2% of the mass of the catalyst. After ultrasonic dispersion of the obtained catalyst ink, the catalyst ink is sprayed on the electrode substrate until the catalyst loading reaches 0.5-4 mg / cm 2 , and obtain the nanosilver catalytic electrode.
7. The nano silver catalytic electrode according to claim 6, characterized in that: The electrode substrate is a carbon-containing electrode substrate such as carbon paper, carbon cloth, carbon felt, etc.
8. An application of the L-cysteine modified nano-silver electrocatalyst according to claim 1 in the in-situ electroconversion of CO2 to efficiently produce CO, characterized in that: L-cysteine-modified nanosilver electrocatalyst was used as a catalyst for the in situ conversion of carbon dioxide to directly reduce carbonate or bicarbonate to carbon monoxide.
9. An application of the nano-silver catalytic electrode according to claim 6 in the in-situ electroconversion of CO2 to efficiently produce CO, characterized in that: The L-cysteine-modified nanosilver catalytic electrode was used as the working electrode and applied to the CO2 in-situ electroconversion system.
10. The use according to claim 9, characterized in that: The electrolyte used in the cathode chamber of the electrolyzer in the CO2 in-situ electroconversion system is a 0.5~3M potassium carbonate or potassium bicarbonate solution; the working electrode in the cathode chamber of the CO2 in-situ electroconversion system converts HCO3 in the cathode electrolyte into - and CO3 2- The carbon-containing components are directly converted into CO, and no additional exogenous carbon-containing gas is introduced into the cathode chamber during the reaction. The current density of the CO2 in-situ electroconversion system is 10~1000mA / cm 2 .
Citation Information
Patent Citations
Quick high concentration synthesizing method of silver nanometer line
CN102423808A
Method for quickly preparing silver nanoparticles through microwave irradiation
CN104772469A
Preparation method and application of PSA (Prostate-specific Antigen) sensor based on silver shell encapsulated L-cysteine capture gold core label
CN106680502A
Method for preparing nano silver particles with controllable grain size uniform size through seed growth method
CN107790741A
Method for green synthesis of silver nanoparticles
CN109570525A
Cited By
Method for preparing antioxidant high-conductivity copper nanoparticles through one-step method
CN120662827A
Amino acid modified copper-based catalyst as well as preparation method and application thereof
CN121250451A